Antimicrobial resistance of Campylobacter isolates recovered from broilers in the Republic of Ireland in 2017 and 2018: an update. Issue 5 (2nd September 2020) - Lynch, C. T.; Lynch, H.; Egan, J.; Whyte, P.; Bolton, D.; Coffey, A.; Lucey, B.
ABSTRACT: 1. Campylobacteriosis is the leading cause of human bacterial gastroenteritis. Broilers are considered the most important source of human Campylobacter infection. In the 2008 European baseline survey Ireland had a 98% prevalence of campylobacter-contaminated broiler carcases. 2. Randomly-selected Campylobacter isolates (296 C. jejuni, 54 C. coli ) recovered in 2017 and 2018, from Irish broiler neck skin and caeca were tested for their resistance to tetracycline, erythromycin, gentamicin, ciprofloxacin, nalidixic acid and streptomycin. 3. Overall, 45% of the Campylobacter spp. isolates tested were resistant to at least one antimicrobial. Tetracycline resistance (38%) was most prevalent in C. jejuni, followed by ciprofloxacin and nalidixic acid resistance (29%). In C. coli, resistance to ciprofloxacin and nalidixic acid (26%) was most prevalent followed by resistance to tetracycline (13%). Gentamicin resistance was undetected and resistance to streptomycin was low for C. jejuni (1%) and C. coli (4%). All C. jejuni isolates examined were erythromycin-sensitive, while 9% of C. coli isolates were erythromycin-resistant. Three multidrug-resistant C. coli isolates were recovered. 4. While antibiotic resistance rates were somewhat similar to figures reported nationally over the past 20 years, the prevalence of tetracycline resistance in C. jejuni has increased. The persistence of substantial ciprofloxacin resistance in the Irish broiler population was noteworthy, despite fluoroquinolones having been banned for growth promotion in Europe since 2006.